'Keep an eye on your friends, even when you don't know them': Drug use and harm reduction in the Goa trance scene in Belgium. (June 2015) - Van Havere, Tina; Tutenges, Sébastien; De Maeyer, Jessica; Broekaert, Eric; Vanderplasschen, Wouter
<x xml:space="preserve">Abstract</x> Aims: The use of illegal drugs is well documented in some alternative, underground music scenes, like the Goa trance scene. The aim of this article is to explore harm reduction practices employed by attendees of the Goa trance scene in order to identify potential pathways for targeted interventions in (underground) music scenes, such as Goa trance. Methods: Following pilot observations at Goa parties, in-depth interviews were conducted with 19 Goa party attendees in Belgium. Respondents were recruited using snowball sampling methods. Findings: Participants reported that solidarity is apparent in the Goa trance scene and is an important variable in minimising drug-related harm, particularly with respect to providing help and support to people in need (communitarian values). On the other hand, personal controls on drug consumption were also employed to minimise harm, such as buying drugs from trusted people, trying to keep drug use limited to weekends and adhering to one's own limits (neo-liberal values). Conclusions: A combination of communitarian and neo-liberal values were employed by drug users in the Goa trance scene in Belgium, and this offers several options for new harm reduction efforts. Approaching drug users as active citizens and enabling resources is a useful way of informing the development of innovative harm reduction strategies. Evaluating enabling resources in settings where drug use occurs will provide additional pathways to harm reduction policies and programs.